2001
DOI: 10.1128/jcm.39.10.3747-3749.2001
|View full text |Cite
|
Sign up to set email alerts
|

Identification of CTX-M-14 Extended-Spectrum β-Lactamase in Clinical Isolates of Shigella sonnei , Escherichia coli , and Klebsiella pneumoniae in Korea

Abstract: CTX-M-14 ␤-lactamase was identified in a stool isolate of Shigella sonnei and in blood isolates of Escherichia coli (one isolate) and Klebsiella pneumoniae (two isolates) from different parts of Korea. The amino acid sequence differed by one amino acid from CTX-M-9 (Ala-2313 Val) and was identical to that of ␤-lactamases recently found in China and Japan.Because resistance is more than locally relevant with increasingly mobile populations and since unique resistance mechanisms may evolve anywhere antibiotics a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
96
1
4

Year Published

2002
2002
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 126 publications
(103 citation statements)
references
References 10 publications
2
96
1
4
Order By: Relevance
“…This observation is in good agreement with the previous publication of Bradford et al (10) reporting the location of genes encoding CTX-M-5 on small non-self-transferable plasmids. It may also explain the relatively low proportion of CTX-M-5-producing isolates compared to those bearing CTX-M-3 and Neither CTX-M-8-nor CTX-M-9-related enzymes were found in this study, although in recent years ESBLs of the latter genetic group were found in other European countries (Spain [9,11,35], France [18,36], and the United Kingdom [Alobwede et al, letter]) as well as in Asian countries (Japan [41], China [14], Taiwan [22,44], Korea [28], and Vietnam [13]) and Brazil (8).…”
Section: Resultsmentioning
confidence: 63%
“…This observation is in good agreement with the previous publication of Bradford et al (10) reporting the location of genes encoding CTX-M-5 on small non-self-transferable plasmids. It may also explain the relatively low proportion of CTX-M-5-producing isolates compared to those bearing CTX-M-3 and Neither CTX-M-8-nor CTX-M-9-related enzymes were found in this study, although in recent years ESBLs of the latter genetic group were found in other European countries (Spain [9,11,35], France [18,36], and the United Kingdom [Alobwede et al, letter]) as well as in Asian countries (Japan [41], China [14], Taiwan [22,44], Korea [28], and Vietnam [13]) and Brazil (8).…”
Section: Resultsmentioning
confidence: 63%
“…Table 1 lists the bacterial strains used in this study and the ␤-lactamases that they produce. The enzymes produced by previously unpublished strains were identified by isoelectric focusing, PCR amplification, cloning, and sequencing, as described previously (1,19,28,36). Plasmids were transferred to porin-deficient K. pneumoniae strain C2 (24) by conjugation (16).…”
Section: Methodsmentioning
confidence: 99%
“…국내에서는 처음으로 2001년 CTX-M-14를 생성하는 E. coli와 K. pneumoniae가 보고되었으며 [21], 2003년 전국 13개 병원에서 분리된 E. coli의 9%가 ESBL을 생성한다고 보고하 였다 [23].…”
Section: 서 론unclassified
“…국내에서도 2002년 전국 13개 병원을 대상으로 조사한 ESBL 출현 현황에서 E. coli와 K. pneumoniae 가 CTX-M (CTX-M-3, CTX-M-14, CTX-M-15) 유전자를 보유 하고 있다고 하였다 [2,21].…”
Section: 서 론unclassified